Effects of different recruitment maneuvers on bacterial translocation and ventilator-induced lung injury - TÜRKÖZ, HÜSEYİN KEMAL (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2015)
BACKGROUND: Investigated in the present study were the effects of various recruitment maneuvers (RMs) using the same inflation pressure-time product on bacterial translocation from lung to blood, and ventilator-induced lung injury (VILI). METHODS: Tracheotomy was performed on anesthetized rats, and ventilation was initiated using pressure-controlled mode. Subsequently, Pseudomonas aeruginosa was inoculated through the tracheotomy tube and ventilated for 30 minutes before rats were randomly separated into 4 groups. Group 1 underwent sustained inflation (SI), Group 2 underwent low-pressure SI, Group 3 underwent modified sigh, and Group 4 was a control group. Blood cultures were taken at baseline, 15 minutes after randomization (after each RM for the first hour), and finally at 75 minutes after the last RM. The rats were euthanized and the lungs were extirpated. The left lung was taken for measurement of wet: dry weight ratio, and the right lung was used for pathologic evaluation. RESULTS: Positive blood cultures were found to be higher in Group 3 at early study periods. Total pathological scores were also higher in Group 3. CONCLUSION: Higher severity of ventilator-induced lung injury occurred in the modified sigh group, evidenced by bacterial translocation and results of histopathological evaluation.
Keywords: Bacterial translocation; mechanical ventilation; recruitment maneuver; SIGH; ventilator-induced lung injury; MECHANICAL VENTILATION; SUSTAINED INFLATION; TIME; PRESSURE; STRATEGY